1976
DOI: 10.1246/bcsj.49.821
|View full text |Cite
|
Sign up to set email alerts
|

The Photo-induced Diels-Alder Reaction of 2-Cycloocten-1-one and 2-Cyclohepten-1-one

Abstract: trans-2-Cycloocten-1-one and trans-2-cyclohepten-1-one, which are supposed to be formed by the ultra-violet irradiation of cis-2-cycloocten-1-one and cis-2-cyclohepten-1-one, give Diels-Alder addition products with cyclopentadiene and isoprene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 3 publications
2
19
0
Order By: Relevance
“…The reaction of cyclooct-2-enone with 1,3-cyclopentadiene was previously reported to yield a single product. 12 Under our conditions, we did not observe a single product but a mixture of two diastereoisomers (9e/9e′) in a ratio that was similar to the dr of the cyclohept-2-enone addition (Scheme 6, 7a/7a′). Eventually, the Diels−Alder reaction was performed with 8,9-dihydrobenzocyclohepten-5one which also reacted cleanly to products 9f/9f′ upon irradiation.…”
Section: ■ Results and Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…The reaction of cyclooct-2-enone with 1,3-cyclopentadiene was previously reported to yield a single product. 12 Under our conditions, we did not observe a single product but a mixture of two diastereoisomers (9e/9e′) in a ratio that was similar to the dr of the cyclohept-2-enone addition (Scheme 6, 7a/7a′). Eventually, the Diels−Alder reaction was performed with 8,9-dihydrobenzocyclohepten-5one which also reacted cleanly to products 9f/9f′ upon irradiation.…”
Section: ■ Results and Discussionmentioning
confidence: 50%
“…The minor differences in the spectroscopic properties of the isoprene adducts 3d and 3d′ may have been difficult to detect by the techniques available in the 1970s, which in turn accounts for a previous report on regioselective formation of 3d. 12 A similar observation as with isoprene was also made with myrcene which gave the transfused products 3e and 3e′ as a mixture of inseparable regioisomers. The reaction scale was irrelevant for the yields, which were consistently good to excellent.…”
Section: ■ Results and Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Trans cycloheptenone was found to react in the dark with alcohols to form products with the stereochemistry expected from a 1,4 addition across trans double bonds. Under identical conditions the cis isomer did not react with these nucleophiles. , Quenching experiments demonstrated that the singlet trans isomer was the chemically active species. , The use of trans cycloheptenone and its benzoannelated derivatives in intermolecular [4 + 2] cycloadditions with cyclopentadiene and furan afforded diastereomeres due to an endo / exo approach of the diene. To our knowledge the only report using an unsymmetrical diene describes the use of isoprene and only the regioisomer expected from FMO theory was observed for the Diels−Alder product . An intramolecular variant was described by Dorr and Rawal .…”
Section: Introductionmentioning
confidence: 99%